The relationship between anxiety and PTSD with the mediating role of mental rumination in people under violence - Nikoonamnezami, Tandis; Mehdipour Kiabani, Zhila; Tabatabaee, Mosa; Khalili, Pouna; Khalili, Parniyan (Journal of Indonesian Psychological Science (JIPS), 2024)
People who experience violence suffer physical and psychological harms, including anxiety, and PTSD. The aim of this study was to determine the mediating role of rumination in the relationship between anxiety and PTSD in Individuals exposed to violence. The method was correlation and structural equation modeling. A total of 210 individuals exposed to violence were selected. Participants completed three questionnaires. Data analysis was conducted using the SPSS and AMOS. The results showed that anxiety and PTSD symptoms were strongly correlated (r = 0.808, p < 0.01), as well as anxiety and rumination (r = 0.532, p < 0.01). Additionally, a moderate correlation was found between rumination and PTSD symptoms (r = 0.379, p < 0.01). The results of study demonstrate a relationship between anxiety and PTSD, with the mediating role of rumination. In addition, positive relationships were found between both rumination and PTSD, and anxiety and rumination. Furthermore, the results indicated a positive and significant relationship between anxiety and PTSD. Rumination links PTSD and anxiety, highlighting importance of mental health interventions. KEY WORDS: anxiety, post-traumatic stress disorder, rumination, trauma, violence